Religious beliefs and perspectives of afterlife and the acceptance of death cancer patients. - Belleza, George Fabe Emmanuel F.
The study was conducted to describe the religious beliefs, practices, perspectives of afterlife and to determine the acceptance of death of cancer patients. Ten (10) cancer patients at Iloilo served as respondents of the study. Among the different religions in the Philippines, Roman Catholic was the dominant religion among the participants. The respondents answered questionnaires, which consisted of the Brief Religious Inventory, the Belief in Afterlife Scale (BA) and Death Anxiety Scale (DAS). Results of the Study showed that the cancer patients had high levels of religious belief and high levels of belief in afterlife. Majority of the participants scored low levels of death acceptance. The cancer patients all believed in God and life after death however, the majority of the patients were still afraid to die.